Exploring the digital marketing practices in the Greek retail sector - Maria Argyropoulou; Dimitris Folinas; Dionisia Tzavara; Chris Grose; Constantinos Charisis (CES Working Papers, 2021)
The development of technology has made great leaps in the lives of people. Digital marketing is now an integral part of every business, irrespective of its size and nature. The growing importance of digital marketing has affected the way businesses promote their offerings to old and new customers. The goal of digital marketing is to make the most of the available practices to target and reach the right users, attract their attention, make a sale, and achieve overall customer satisfaction. Through a survey of 100 e-tailers, this study examines the internal and external factors that influence the adoption of digital marketing practices in the Greek retail sector. The results of a regression analysis show that business resources and related practices have a positive impact on the benefits that can be achieved through the adoption of e-marketing practices.
Keywords: 330; digital marketing; e-commerce; retail sector